Transformation of Digital Health: Advancing Telerehabilitation with Smartwatch Technology - Marwa Asim; Muhammad Ehab Azim; Furqan Ahmed Siddiqi; Farooq Azam Rathore (Journal of the Pakistan Medical Association, 2024)
The emergence of innovative electronic devices has revolutionized the role of medicine, specifically telemedicine and telerehabilitation. A smartwatch is similar in shape to a traditional wristwatch with a built-in, networked computer with an array of sensors. The use of smartwatches has provided healthcare workers with new opportunities for monitoring and managing health. Monitoring of vitals like heart rate, blood pressure, and oxygen saturation, has been made possible by the help of smartwatches. These features provide the wearer with a real-time picture of their health. Monitoring of vital health parameters over time can help detect irregularities in health status and can also be used for remote patient monitoring. This enables healthcare professionals to monitor their patient’s health from anywhere. Smartwatches are being used in physical rehabilitation nowadays for monitoring vitals during physical therapy and tracking the progress of the wearer. This mini-review discusses insights into the benefits of using smartwatches in healthcare, and focuses on the evolving role of smartwatches in telerehabilitation.